Does Import Protection Discourage Exports? - Tokarick, Stephen (Washington, D.C. : International Monetary Fund, 2006)
This paper points out that while many developing countries seek to increase their export earnings, they have not embraced fully the notion that their own pattern of import protection hurts their export performance. The paper quantifies the extent to which import protection acts as a tax on a country's export sector and finds that for many developing countries, the magnitude of the implicit tax is substantial-about 12 percent, on average, for the countries studied. The paper also illustrates the effects of various tariff-cutting scenarios in the Doha Round on export incentives and concludes that, in general, developing countries could increase their export earnings by reducing their own import tariffs, but countries must be careful about how these tariff reductions are achieved. For example, tariff-cutting schemes that exempt certain sectors could actually be harmful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet